2020
DOI: 10.5144/0256-4947.2020.408
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with facial weakness following surgery for benign parotid disease: a retrospective multicenter study

Abstract: BACKGROUND: Facial nerve weakness is the most common and most concerning complication after parotidectomy. Risk factors for this complication following surgery for benign diseases remain controversial. OBJECTIVE: Review the frequency and prognosis of facial nerve weakness after parotidectomy and analyze potential risk factors. DESIGN: Retrospective review of medical records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Some authors suggested a possible higher rate of facial weakness in children [ 2 ]. Contrarily, in a previous study by the primary author of the present study, age was not a risk factor for temporary or permanent facial weakness [ 14 ]. Similarly, Owusu et al concluded that age was not predictive of facial weakness in their review of 43 pediatric parotidectomies [ 13 ].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Some authors suggested a possible higher rate of facial weakness in children [ 2 ]. Contrarily, in a previous study by the primary author of the present study, age was not a risk factor for temporary or permanent facial weakness [ 14 ]. Similarly, Owusu et al concluded that age was not predictive of facial weakness in their review of 43 pediatric parotidectomies [ 13 ].…”
Section: Discussionmentioning
confidence: 49%
“…The rate of temporary facial weakness in our study was 33%. Previous studies on both adult and pediatric parotidectomies reported similar rates ranging from 9.3% to 64.6% [3,[12][13][14]. Some authors suggested a possible higher rate of facial weakness in children [2].…”
Section: Figure 1: Distribution Of Pediatric Parotid Lesions By Age and Type Of Pathologymentioning
confidence: 81%
“…Dexamethasone‐treated patients also regained facial function slower than controls (median recovery time: 60 vs. 150 days). Retrospective studies have also concluded that steroids may not play a role in the recovery of facial weakness 38,41 …”
Section: Discussionmentioning
confidence: 99%
“…Rates of transient paralysis after parotidectomy range from 10% to over 50% whereas permanent paralysis is less common at 0%–8% 31,38 . Paralysis rates may vary by tumor size and the indications for surgery, only some of which are modifiable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation